Brucellosis manifesting as reversible ataxia caused by SIADH-related hyponatremia - Baraa Habib (16936870) (2021)
Brucellosis is an infectious disease commonly presents with fever, fatigue, arthralgia, and muscle pain. Nonetheless, hyponatremia and its related symptoms have been reported as presenting features of brucellosis. Herein, we report a 56-year-old male presenting with ataxia and SIADH-related hyponatremia induced by brucellosis. The ataxia improved following hyponatremia correction. Up to our knowledge, this is the first case of reversible cerebellar ataxia occurring in the setting of brucellosisrelated SIADH. Other Information Published in: IDCases License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.idcr.2020.e01043